ANALYSIS OF THE CARRYING CAPACITY OF RESIDENTIAL LAND IN THE NEW CAMPUS AREA OF UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA - Abdul Galib; Sudarwin Kamur (Geographica: Science and Education Journal, 2023)
Land carrying capacity is an important thing that must be considered in regional development planning so that it is able to support sustainable land use activities. The increasing growth of new residential in Tanggetada District will trigger an increase in the need for land. This will indirectly reduce the area of productive land such as agricultural land to be converted into residential land. The aim of this research is to analyze the carrying capacity of residential land in the new campus area of Universitas Sembilanbelas November Kolaka, Tanggetada District, Kolaka Regency. The method used in this research is the quantitative descriptive method. Data analysis uses the Permenlh formula and Geometric formula. The results of this research show that the carrying capacity of settlements in Tanggetada District in 2021 is 134.9. These results indicate that the land in the new USN Kolaka campus area is still very capable of supporting settlements. The predicted carrying capacity of surface land in the USN Kolaka New Campus Area in Tanggetada District in 2030 is 68 and in 2040 it is 29 which indicates that the USN Kolaka new campus area is able to support residents to settle (build houses) in the area in 2030 and 2040 The predicted population in 2030 is 23,949 people and the predicted population in 2041 is 55,306 people.